2014
DOI: 10.1007/s11483-014-9378-8
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties of Chitin and Chitosan Produced from Medicinal Fungus (Fomitopsis pinicola)

Abstract: Fomitopsis pincola, which is used as a medicinal fungus in Asia, is widespread throughout the temperate Northern Hemisphere. The fungus's chitin structure was isolated and characterized in this study. It was found that 30.11 % of the dry weight of the fungus consisted of chitin, a very high portion. The chitosan yield from the chitin was 71.75 %. It was calculated that chitin acetylation was 72.5 % and that deacetylation of chitosan was 73.1 %. The maximum temperature of degradation (DTGmax) recorded for the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 26 publications
4
30
1
Order By: Relevance
“…The DTGmax value determined between 300 -400 o C for α-chitin [35]. The DTGmax values were reported around 350 °C for crustaceans, around 380°C for insects, 341 o C for F. pinicola and 342 o C for X. parietina [22,25,26,31,33]. A similar result was recorded for potato beetle (Leptinotarsa decemlineata) larvae (DTGmax: 307 °C) by Kaya et al [36].…”
Section: Tgasupporting
confidence: 70%
See 2 more Smart Citations
“…The DTGmax value determined between 300 -400 o C for α-chitin [35]. The DTGmax values were reported around 350 °C for crustaceans, around 380°C for insects, 341 o C for F. pinicola and 342 o C for X. parietina [22,25,26,31,33]. A similar result was recorded for potato beetle (Leptinotarsa decemlineata) larvae (DTGmax: 307 °C) by Kaya et al [36].…”
Section: Tgasupporting
confidence: 70%
“…The author reported that the chitin contents of Agaricus bisporus, Pleurotus ostreatus and L. edodes were 6.67%, 3.78% and 8.07% for the pileus and 7.31%, 2.8% and 6.55% for the stipes, respectively. Dry weight chitin content of a medicinal fungus Fomitopsis pinicola was found to be 30.11 % and the chitosan yield of this chitin was 71.75 % [25]. Finally, the dry weight chitin content of a lichen species Xanthoria parietina consisting of fungi and algae was determined as 4.23% by Kaya et al [26].…”
Section: Chitin Contentmentioning
confidence: 97%
See 1 more Smart Citation
“…After the addition of silica to the chitosan-ZnCl 2 solution, the bands of 3364 and 3307 cm − 1 in the spectrum of CH_Zn4 are shifted to 3396 and 3310 cm − 1 , respectively, which supports interaction. The spectrum of pure chitosan is characterized by the band of amide group, (C=O), (amide I) at 1655 and 1560 cm − 1 (-NH-), (amide II) band, as well as with the band at 1590 cm − 1 corresponding to the -N-H bending vibrations [45] of primary amine group [58,59]. If the acetic acid played a role of the chitosan's solvent, obtained chitosan acetate films should be washed in ammonia water solution and methanol to remove acetate residues and obtain pure chitosan films [58].…”
Section: Ftirmentioning
confidence: 99%
“…Chitin is the most widespread natural polysaccharide. It is the main component of the exoskeletons of many invertebrates [82], but is also found in the cell walls of fungi and bacteria, where it performs protective and supporting functions [83]. Chitin is a rigid semi-transparent polymer, insoluble in water, resistant to the effects of dilute acids, and alkalis, and to alcohol and other organic solvents.…”
Section: Natural Polymersmentioning
confidence: 99%